Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21649/akemu.v24i1.2334
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Obesity with Hypertension in Medical Students

Abstract: The relationship between obesity and hypertension has long been recognized. Overweight and obesity are disorders of balance of energy affecting people of various ethnic groups, age and socio–economic statuses. It has been found that obesity is closely associated and correlated with hypertension. Preventive strategies for obesity may offer a cost-effective approach towards lowering blood pressure. Objectives: To determine the frequency of obesity according to body mass index and waist hip ratio and its relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In accordance with this study, study by Aftab et al .,[ 17 ] reported that HTN was present in 14 (35.9%) obese I and 7 (17.9%) obese II subjects, 6 (15.4%) overweight, 12 (30.8%) normal weight students. Also, in a study by Chhabra et al .,[ 16 ] a significant relation between BP and BMI was observed which was consistent with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this study, study by Aftab et al .,[ 17 ] reported that HTN was present in 14 (35.9%) obese I and 7 (17.9%) obese II subjects, 6 (15.4%) overweight, 12 (30.8%) normal weight students. Also, in a study by Chhabra et al .,[ 16 ] a significant relation between BP and BMI was observed which was consistent with our study findings.…”
Section: Discussionmentioning
confidence: 99%